IMPLEMENTASI SISTEM INFORMASI NILAI MATA PELAJARAN BERBASIS WEB DENGAN FITUR PEMILIHAN SISWA BERPRESTASI AKADEMIK MENGGUNAKAN METODE PROFILE MATCHING - Wirdhayanti, Wirdhayanti; Hendra, Syaiful; Rasmita, Hajra; Idhamsyahreza, Idhamsyahreza (Foristek, 2023)
The use of a computerized system saves data processing time, data storage can be safer than manual storage and can reduce the human error factor. There fore the use of information systems as a data management tool must be designed according to existing needs. This is what is needed by SMP N 5 Palu because the management of existing subject values is still done manually so it has weaknesses, including recording grades, making attendance reports, and making report cards which is quite difficult to collect lesson values from each teacher so that the recording process becomes hampered and The process of selecting outstanding students which has been carried out so far by the school still has several weaknesses as a result it raises several problems, including the processing of data for selecting outstanding students which takes a long time and the possibility of human error occurring in data processing. Therefore, a web-based subject score information system was created with the feature of selecting outstanding students using the Profile Matching method. This system was developed using the Profile Matching method, which is a multi-criteria decision-making method that has very simple calculations but has good level of selectivity in determining an alternative. The results of this study are in the form of applications that can help provide information on subject values and decisions in determining students' academic achievements at the school.